If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2(5y+6)-3=4y+2
We move all terms to the left:
2(5y+6)-3-(4y+2)=0
We multiply parentheses
10y-(4y+2)+12-3=0
We get rid of parentheses
10y-4y-2+12-3=0
We add all the numbers together, and all the variables
6y+7=0
We move all terms containing y to the left, all other terms to the right
6y=-7
y=-7/6
y=-1+1/6
| -0.55=0.2(x-61/2) | | (5b*2)+(4b*2)=72 | | 8x+12=108+6x | | a/74=6.79 | | 15=3v-15 | | y2+12y=–7 | | −v−4=3v | | 5v+12=13 | | 5v2+12v=13 | | 3x+21=123 | | 3x+14=4x-26 | | 12(9x+3)=1008 | | 6.3r=45.36 | | 85z −18=824−2z | | a+21=-9 | | 8(2^x*3)=48 | | 14=-8m | | z+45=33 | | 7x=30-2 | | 7y−1=3y+11 | | 11x-9/3-10=3 | | 14n=n | | x/6-9=5 | | 7x/6-12=156 | | 15+p=-12 | | 3.25=2.5+r | | 15n-6.5=53.3 | | 15x/8+7=37 | | x/8=15/23 | | 90x=80x+75 | | w/14=6 | | 8+3(4x-6)=9-5(2x+1) |